Studi Karakteristik Sistem Instalasi Pipa Udara Bertekanandan Instalasi Pipa Gas O2 di Bengkel Pipa dan Plat Politeknik Negeri Bengkalis - Siswandi B; Jupri; Muhammad Sidik Purwoko (ABEC Indonesia, 2022)
Piping installation is a unified series of pipes or systems to drain fluid to the desired place by using pipes according to specifications. The piping system is usually equipped with components such as valves, flanges, elbows, branches, nozzles, reducers, supports, insulation and others. The Department of Marine Engineering is one of the majors at the Bengkalis State Polytechnic with facilities and infrastructure, one of which is Pipe and Plate Workshop. The production activities and the teaching and learning process cannot be separated from the plate cutting and painting processes that require compressed air and O2. For the effectiveness of the activities in the Pipe and Plate Workshop, a system for installing compressed air and O2 is carried out. Then the pipe installation system is tested based on the needs of the work carried out at the Pipe and Plate Workshop. Based on the test results on the air pipe installation system, the pressure drop at the outlet valve to the inlet pressure is obtained, namely outlet 1 of 0.1 bar, outlet 2 of 0.3 bar and outlet 3 of 0.4 bar. For the O2 pipe installation system, it is found that the output pressure drop (outlet) to the inlet pressure is large, namely outlet 1 of 0.38 kg/cm2 and outlet 2 of 0.51 kg/cm2.